Institutions, wages, and inequality: The case of Europe and its periphery (1500-1899) - CHOR, Davin (Institutional Knowledge at Singapore Management University, 2005)
This paper explores the long-run relationship between institutions and wage outcomes in Europe and its periphery. I find that cities that exercised stronger institutional protection of private property experienced: (i) higher levels of both skilled and unskilled real wages, as well as (ii) lower levels of inequality as measured by the skilled-unskilled wage ratio. While the first result corroborates existing work on the positive growth effects of better institutions, the second finding is more novel to the literature. Some explanations are proposed for how stronger institutions can cause an increase in the relative supply of skilled workers, thus lowering wage inequality.